Inactivation of the Thymidylate Synthase thyA in Non-typeable Haemophilus influenzae Modulates Antibiotic Resistance and Has a Strong Impact on Its Interplay with the Host Airways - Rodríguez-Arce, Irene; Martí, Sara; Euba, Begoña; Fernández-Calvet, Ariadna; Moleres, Javier; López-López, Nahikari; Barberán, Montserrat; Ramos-Vivas, José; Tubau, Fe; Losa, Carmen; Ardanuy, Carmen; Leiva, José; et al. (Frontiers in Cellular and Infection Microbiology, 2017)
Antibacterial treatment with cotrimoxazol (TxS), a combination of trimethoprim and sulfamethoxazole, generates resistance by, among others, acquisition of thymidine auxotrophy associated with mutations in the thymidylate synthase gene thyA, which can modify the biology of infection. The opportunistic pathogen nontypeable Haemophilus influenzae (NTHi) is frequently encountered in the lower airways of chronic obstructive pulmonary disease (COPD) patients, and associated with acute exacerbation of COPD symptoms. Increasing resistance of NTHi to TxS limits its suitability as initial antibacterial against COPD exacerbation, although its relationship with thymidine auxotrophy is unknown. In this study, the analysis of 2,542 NTHi isolates recovered at Bellvitge University Hospital (Spain) in the period 2010-2014 revealed 119 strains forming slow-growing colonies on the thymidine low concentration medium Mueller Hinton Fastidious, including one strain isolated from a COPD patient undergoing TxS therapy that was a reversible thymidine auxotroph. To assess the impact of thymidine auxotrophy in the NTHi-host interplay during respiratory infection, thyA mutants were generated in both the clinical isolate NTHi375 and the reference strain RdKW20. Inactivation of the thyA gene increased TxS resistance, but also promoted morphological changes consistent with elongation and impaired bacterial division, which altered H. influenzae self-aggregation, phosphorylcholine level, C3b deposition and airway epithelial infection patterns. Availability of external thymidine contributed to overcome such auxotrophy and TxS effect, potentially facilitated by the nucleoside transporter nupC. Although thyA inactivation resulted in bacterial attenuation in a lung infection mouse model, it also rendered a lower clearance upon a TxS challenge in vivo. Thus, our results show that thymidine auxotrophy modulates both the NTHi host airway interplay and antibiotic resistance, which should be considered at the clinical setting for the consequences of TxS administration.